Mechanical and Water Absorption Characteristics of Sisal Fiber Reinforced Polypropylene Composite - Eyasu Ferede; Desalegn Atalie (Journal of Natural Fibers, 2022)
The aim of this study is to investigate the effect of fiber loading on mechanical and water absorption characteristics of composites made from sisal fiber and polypropylene matrix targeted for use in bathroom wall tile applications. The amount of fiber content in the composites was varied from 10%, 20%, 30%, and 40% to 50% by weight. The composites were manufactured by melt-mixing method. The effects of fiber loading on various composite characteristics were investigated using tensile strength, tensile modulus, flexural strength, flexural modulus, impact strength, compressive strength, and water absorption. With the increase of fiber content, properties, such as tensile strength, tensile modulus, flexural strength, flexural modulus, impact strength, and compressive strength increases up to optimum level, whilst decrement in these properties were observed after the optimal level. The maximum tensile strength of 52.69 MPa, tensile modulus of 1.1 GPa, flexural strength of 127.8 MPa, flexural modulus of 6.22 GPa, impact strength of 10.195 KJ/m2 and compressive strength 137.7 MPa were obtained. Water absorption rate increased with increase in the fiber weight proportion due to the hydrophilic character of the sisal fiber. From the result of this study, it can be concluded that the optimal mechanical and water absorption properties were achieved at 30% fiber content.